ANALYSIS OF POTENTIAL, PROBLEM, AND DEVELOPMENT STRATEGY OF MSMES TENUN IKAT KEDIRI - Subagyo Subagyo (UPT Penerbitan Universitas Jember)
This study aims to identify and obtain in-depth data or information about the potential and problems of MSMEs Tenun Ikat in Kediri, so as to determine the right strategy in the framework of its development. The study used primary and secondary data. Primary data was obtained through field survey by giving a questionnaire and conducting interviews to 15 Tenun Ikat businessmen in Kediri. Secondary data is obtained from various sources of publication. Data were analyzed using descriptive analysis and SWOT analysis. The result of SWOT analysis shows that the position of MSMEs Tenun Ikat Kediri is in diagram 3, meaning that MSMEs Tenun Ikat Kediri faces a huge market opportunity to be developed, but on the other hand it faces internal constraints / weaknesses. The focus of corporate strategy is to minimize internal weakness of the company, so as to seize greater market opportunities. Therefore, the weaknesses that currently still become an obstacle to the development of MSMEs Tenun Ikat Kediri need to interfere from several parties, whether entrepreneurs, local government, relevant agencies (Regional Planning Board, Department of Cooperatives and SMEs, Industry and Commerce) Banking and Universities.